OPTIMIZATION OF METHODS OF ROENTGEN DIAGNOSTICS IN PATIENTS WITH NECROTIZING ENTEROCOLITIS - Дударев, Вадим Александрович; Галактионова, Марина Юрьевна; Портнягина, Эльвира Васильевна (Mother and Baby in Kuzbass, 2019)
Necrotizing enterocolitis (NEC) is the most frequent emergency pathology of newborns, that always requires emergency surgery in cases of perforation. At the present time, there are NEC of mature and premature newborns, as well as isolated perforations. In these groups NEC has a different clinical manifestations development – from fulminant and acute to intermittent and latent with pronounced stages by Bell. Active examination of the most significant diagnostic factors on early stages of disease, is the one of the first tasks of neonatologists and pediatric surgeons. Roentgen diagnostic is the most reliable diagnostic method in case of appearance of clinical picture of necrotizing enterocolitis. Analysis of method of roentgen-contrast examination of gastrointestinal tract was held in the study. In patients with NEC was used starch-contrast mixture of our development (SCM). The use of SCM has its advantages: simplicity and accessibility in use, high diagnostic informativeness, identification of objective signs of NEC, for 2-3 hours before examination, allows to evaluate the severity of patient’s condition in early terms, and to timely adjust the treatment.